Influence of nickel-based buttering material on welded joint between SA508 low alloy steel and 304LN stainless steel. (February 2022) - Ravikiran, K.; Mehtani, H.; Sivaprasad, K.; Prasad, M.J.N.V.; Kumar, Suranjit; Singh, P.K.; Ghosh, M.
Abstract: Dissimilar metal welded joints were fabricated between SA508 low alloy and 304LN stainless steel using IN82, IN182, and IN152 as buttering alloys. In-situ tensile testing of the welds demonstrated that the crack initiation and propagation were away from the fusion boundary between low alloy steel and buttering material. The heterogeneities like clustered lath martensite with high dislocation density, Type-I boundary, and Type-II boundary near the interface have a meager role in influencing the tensile properties of the welds. On the contrary, grain structure and second phase distribution in re-solidified buttering alloy played a dominant role in determining the tensile properties of welds. This understanding may pave the way to modify the welding parameters, select appropriate welding consumables, and explore the failure-prone location for such kind of transition joints. Graphical abstract: Image 1 Highlights: Low alloy steel and 304LN stainless steel was joined by conventional V-groove welding using three different Inconel alloys i.e. IN82, IN182 and IN152. With respect to available open domain literatures, unique aspects of the manuscript may be described as. In-depth investigation on evolved microstructure near fusion boundary between low alloy steel and buttering material to eradicate the ambiguity, that has been appeared in published literatures. Understanding the sequence of deformation and identifying the weakest region across fusion boundary; thus, a confirmation about the failure prone region, which was to some extent confusing previously. Microstructure-mechanical properties co-relation to explore the best possible welding consumable for achieving a reliable transition joint.